Development Social Welfare and Justice: 21st Century Education Devise: Pembangunan Kesejahteraan Sosial dan Keadilan: Perangkat Pendidikan Abad 21 - Don, Yahya (Pedagogia : Jurnal Pendidikan, 2018)
This procedures is discussed about development social welfare and justice through education transformation in the 21st century. The development of social welfare and justice particularly in the context of education transformation within the framework of the modern education system demand leadership of teachers and leaders adaptable with the changes and existing condition in the social welfare and justice recognize the needs to be effective education Leaders. In accordance to development social welfare and justice, the requirements to familiar with research findings on the knowledge, skills, implementation tools, methods, and strategies useful for formulating vision direction and positive learning in the 21st century are necessities. This paper also discussed an emerging role and challenging of the 21st century education teachers and leaders required to transform the social welfare and justice. Major transformations required the 21st century leader to be a powerful learner, visionary, instructional and influential people. The 21st century leader is essential to have tools and methods to expect, inspect, direct, respect and reflect. The development social welfare and justice will need to concentrate on curriculum development, formative assessment, instruction, technology adaptability, culture and climate, professional development as well as effective supervision to make a massive improvement in development social welfare and justice